Nutritional Strategies to Mitigate Enteric Methane Emissions in Dairy Buffaloes - Pugliese, Gianluca; Losacco, Caterina; Laudadio, Vito; Puvača, Nikola; Filipponio, Nicola; Valentini, Luisa; Tufarelli, Vincenzo (Journal of Buffalo Science, 2026)
Water buffalo (Bubalus bubalis) is an important multi-purpose ruminant species providing animal-based food and supporting rural communities’ economic sustainability, especially in Asia. However, the specialized microbial consortium responsible for fiber degradation within the rumen also contributes to environmental degradation through enteric methane (CH4) generation, making methanogenesis reduction a pivotal challenge for the sector’s sustainable development. As CH4 results from ruminal microbiota metabolism, nutritional interventions are regarded as having the greatest mitigation potential, although most studies have focused on cattle, and buffalo-specific data remain scarce. The literature offers a broad range of effective strategies, including modifications to the forage-to-concentrate ratio and dietary lipids and phytochemicals, with mitigation gains ranging from 10 to 80%. These strategies can reduce methanogenesis through several mechanisms, including direct inhibition of methanogenic archaea and protozoa, shifting fermentation pathways, or diverting hydrogen toward alternative sinks. However, in vivo studies in buffalo remain scarce, underscoring the need for future research that considers all CH4-relevant parameters within a holistic framework. The available literature remains limited and fragmented, underscoring the need for further research to understand species-specific responses and develop effective mitigation strategies under practical conditions. Therefore, this review comprehensively summarises current knowledge of nutritional interventions that have been shown to reduce CH4 production in buffalo without adverse effects on welfare or productivity. Additionally, given their influence on CH4 production and implications for species-specific responses, the main differences in digestive morphology, physiology, and rumen microbial ecology between buffalo and cattle are discussed, providing a comparative perspective to evaluate whether mitigation approaches developed for bovines can be effectively applied to buffaloes.